A leadership discovery : enhancing Finnish youth football coaches' effectiveness through the Transformer Research Project - Lewis, Garry (2019)
It is well established that coaches benefit from coaching development programs (Côté & Turnnidge, 2017). Research reflects the strength that Transformational Leadership (TFL) theory holds great promise when embedded in the youth sport setting. Collaboration between researchers, communal sport organizers, and national sport policy makers represents an intriguing, yet marginal aim throughout the literature to effect coaches’ interpersonal and intrapersonal knowledge domains (Lefebvre et al., 2016). Thus, the Transformer Research Project’s purpose was to fill the gap — through planning, implementing, describing, and evaluating a pilot leadership program within the Finnish youth football context — that included a series of interviews, observations, feedback sessions, journaling, and one workshop.